2021
DOI: 10.1007/s11255-020-02770-x
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of video improve patient satisfaction in the consent process for local-anaesthetic urological procedures?

Abstract: To assess patient satisfaction with the use of Portable Video Media (PVM) for the purpose of taking informed consent for common urological outpatient procedures performed under local anaesthesia. MethodsPatients undergoing the following procedures were approached for recruitment: flexible cystoscopy with or without biopsy, transrectal ultrasound-guided prostate biopsy or flexible cystoscopy with insertion or removal of a ureteric stent. Audio-visual media were developed for each procedure, with each script tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The rest ( n = 2) [ 10 , 16 ] included parents who consented on behalf of their children who were undergoing surgical procedures. Most studies used a two-arm parallel RCT design ( n = 39) [ 1 , 6 , 7 , 9 , 13 , 14 , 16 , 20 , 23 , 24 , 33 , 39 , 40 , 46 , 52 , 55 , 59 , 62 , 63 , 65 , 72 , 75 , 76 , 78 , 79 , 82 , 85 , 86 , 90 , 91 , 94 , 95 ] to compare a purpose-built digital intervention for the IC process with control groups receiving traditional non-electronic IC practice. Two of these 39 RCTs implemented a cross-over design where participants served as their own controls [ 61 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rest ( n = 2) [ 10 , 16 ] included parents who consented on behalf of their children who were undergoing surgical procedures. Most studies used a two-arm parallel RCT design ( n = 39) [ 1 , 6 , 7 , 9 , 13 , 14 , 16 , 20 , 23 , 24 , 33 , 39 , 40 , 46 , 52 , 55 , 59 , 62 , 63 , 65 , 72 , 75 , 76 , 78 , 79 , 82 , 85 , 86 , 90 , 91 , 94 , 95 ] to compare a purpose-built digital intervention for the IC process with control groups receiving traditional non-electronic IC practice. Two of these 39 RCTs implemented a cross-over design where participants served as their own controls [ 61 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-one of 63 included studies reported the primary outcome, patient satisfaction. Forty-eight publications (76.1%) measured the secondary outcome, patient knowledge gain [ 1 , 2 , 4 , 5 , 9 , 13 , 14 , 16 , 18 , 20 , 24 , 25 , 27 , 28 , 33 , 34 , 39 , 42 , 46 , 52 , 54 , 55 , 59 , 62 , 63 , 65 , 66 , 71 , 75 , 76 , 78 , 79 , 82 , 85 91 , 94 , 95 ]. Of the 109 outcomes measured across the 63 publications, only 10 (9.2%) were assessed using validated instruments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the digital age, the use of media in learning tends to increase. This condition needs to be adapted early (Moore et al, 2021). During the pandemic, the main educational activities were carried out online (Indrawati, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Instructional video media becomes an effective educational tool (Hapsari et al, 2019;Zuhriyah et al, 2021). Most of the literature in research publications suggests that video media adds to the understanding and attention of a study (Moore et al, 2021). Video media effectively improves natural science learning outcomes for elementary school students (Hanif, 2020).…”
Section: Introductionmentioning
confidence: 99%